Etmopterus samadiae n. sp., a new lanternshark (Squaliformes: Etmopteridae) from Papua New Guinea - White, William T.; Ebert, David A.; Mana, Ralph R.; Corrigan, Shannon (Zootaxa, 2017)
A new species of lanternshark, Etmopterus samadiae (Squaliformes: Etmopteridae), is described from off northern Papua New Guinea, in the western Central Pacific Ocean. The new species resembles other members of the “Etmopterus lucifer” clade in having linear rows of dermal denticles and most closely resembles E. brachyurus from the western North Pacific. The new species occurs along insular slopes between 340 and 785 m depth. The new species can be distinguished from other members of the E. lucifer clade by a combination of characteristics, including length of anterior flank branch markings being slightly shorter than its posterior branch, a longer caudal base marking, and irregular and variable number of black, horizontal, dash-like marks on sides of body. Molecular analysis based on the NADH2 marker further supports the distinction of E. samadiae from other members of the E. lucifer clade.